Non-Invasive Visualization of Ferroelectric Domain Structures on the Non-Polar y-Surface of KTiOPO4 via Raman Imaging - Brockmeier, Julian; Mackwitz, Peter Walter Martin; Rüsing, Michael; Eigner, Christof; Padberg, Laura; Santandrea, Matteo; Silberhorn, Christine; Zrenner, Artur; Berth, Gerhard (Crystals)
Potassium titanyl phosphate (KTP) is a nonlinear optical material with applications in high-power frequency conversion or quasi-phase matching in submicron period domain grids. A prerequisite for these applications is a precise control and understanding of the poling mechanisms to enable the fabrication of high-grade domain grids. In contrast to the widely used material lithium niobate, the domain growth in KTP is less studied, because many standard methods, such as selective etching or polarization microscopy, provides less insight or are not applicable on non-polar surfaces, respectively. In this work, we present results of confocal Raman-spectroscopy of the ferroelectric domain structure in KTP. This analytical method allows for the visualization of domain grids of the non-polar KTP y-face and therefore more insight into the domain-growth and -structure in KTP, which can be used for improved domain fabrication.

“Seeing Is Believing”—In-Depth Analysis by Co-Imaging of Periodically-Poled X-Cut Lithium Niobate Thin Films - Reitzig, Sven; Rüsing, Michael; Zhao, Jie; Kirbus, Benjamin; Mookherjea, Shayan; Eng, Lukas M. (Crystals)
Nonlinear and quantum optical devices based on periodically-poled thin film lithium niobate (PP-TFLN) have gained considerable interest lately, due to their significantly improved performance as compared to their bulk counterparts. Nevertheless, performance parameters such as conversion efficiency, minimum pump power, and spectral bandwidth strongly depend on the quality of the domain structure in these PP-TFLN samples, e.g., their homogeneity and duty cycle, as well as on the overlap and penetration depth of domains with the waveguide mode. Hence, in order to propose improved fabrication protocols, a profound quality control of domain structures is needed that allows quantifying and thoroughly analyzing these parameters. In this paper, we propose to combine a set of nanometer-to-micrometer-scale imaging techniques, i.e., piezoresponse force microscopy (PFM), second-harmonic generation (SHG), and Raman spectroscopy (RS), to access the relevant and crucial sample properties through cross-correlating these methods. Based on our findings, we designate SHG to be the best-suited standard imaging technique for this purpose, in particular when investigating the domain poling process in x-cut TFLNs. While PFM is excellently recommended for near-surface high-resolution imaging, RS provides thorough insights into stress and/or defect distributions, as associated with these domain structures. In this context, our work here indicates unexpectedly large signs for internal fields occurring in x-cut PP-TFLNs that are substantially larger as compared to previous observations in bulk LN.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Photoconduction of Polar and Nonpolar Cuts of Undoped Sr0.61Ba0.39Nb2O6 Single Crystals - Beyreuther, Elke; Ratzenberger, Julius; Roeper, Matthias; Kirbus, Benjamin; Rüsing, Michael; Ivleva, Liudmila I.; Eng, Lukas M. (Crystals)
In the last two decades, variably doped strontium barium niobate (SBN) has attracted a lot of scientific interest mainly due to its specific non-linear optical response. Comparably, the parental compound, i.e., undoped SBN, appears to be less studied so far. Here, two different cuts of single-crystalline nominally pure strontium barium niobate in the composition Sr0.61Ba0.39Nb2O6 (SBN61) are comprehensively studied and analyzed with regard to their photoconductive responses. We present conductance measurements under systematically varied illumination conditions along either the polar z-axis or perpendicular to it (x-cut). Apart from a pronounced photoconductance (PC) already under daylight and a large effect upon super-bandgap illumination in general, we observe (i) distinct spectral features when sweeping the excitation wavelength over the sub-bandgap region as then discussed in the context of deep and shallow trap states, (ii) extremely slow long-term relaxation for both light-on and light-off transients in the range of hours and days, (iii) a critical dependence of the photoresponse on the pre-illumination history of the sample, and (iv) a current–voltage hysteresis depending on both the illumination and the electrical-measurement conditions in a complex manner.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Tricyanidoferrates(−IV) and Ruthenates(−IV) with Non‐Innocent Cyanido Ligands - Jach, Franziska; Wagner, Frank R.; Amber, Zeeshan H.; Rüsing, Michael; Hunger, Jens; Prots, Yurii; Kaiser, Martin; Bobnar, Matej; Jesche, Anton; Eng, Lukas M.; Ruck, Michael; Höhn, Peter (Angewandte Chemie International Edition)
Exceptionally electron-rich, nearly trigonal-planar tricyanidometalate anions [Fe(CN)3]7− and [Ru(CN)3]7− were stabilized in LiSr3[Fe(CN)3] and AE3.5[M(CN)3] (AE=Sr, Ba; M=Fe, Ru). They are the first examples of group 8 elements with the oxidation state of −IV. Microcrystalline powders were obtained by a solid-state route, single crystals from alkali metal flux. While LiSr3[Fe(CN)3] crystallizes in P63/m, the polar space group P63 with three-fold cell volume for AE3.5[M(CN)3] is confirmed by second harmonic generation. X-ray diffraction, IR and Raman spectroscopy reveal longer C−N distances (124–128 pm) and much lower stretching frequencies (1484–1634 cm−1) than in classical cyanidometalates. Weak C−N bonds in combination with strong M−C π-bonding is a scheme also known for carbonylmetalates. Instead of the formal notation [Fe−IV(CN−)3]7−, quantum chemical calculations reveal non-innocent intermediate-valent CN1.67− ligands and a closed-shell d10 configuration for Fe, that is, Fe2−.
Keywords: General Chemistry; Catalysis

Quantifying the coherent interaction length of second-harmonic microscopy in lithium niobate confined nanostructures - Amber, Zeeshan H.; Kirbus, Benjamin; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Thin-film lithium niobate (TFLN) in the form of x- or z-cut lithium-niobate-on-insulator has attracted considerable interest as a very promising and novel platform for developing integrated optoelectronic (nano)devices and exploring fundamental research. Here, we investigate the coherent interaction length lc of optical second-harmonic generation (SHG) microscopy in such samples, that are purposely prepared into a wedge shape, in order to elegantly tune the geometrical confinement from bulk thicknesses down to approximately 50 nm. SHG microscopy is a very powerful and non-invasive tool for the investigation of structural properties in the biological and solid-state sciences, especially for visualizing and analyzing ferroelectric domains and domain walls. However, unlike in bulk lithium niobate (LN), SHG microscopy in TFLN is impacted by interfacial reflections and resonant enhancement, both of which rely on film thickness and substrate material. In this paper, we show that the dominant SHG contribution measured on TFLN in backreflection is the co-propagating phase-matched SHG signal and not the counter-propagating SHG portion as is the case for bulk LN samples. Moreover, lc depends on the incident pump laser wavelength (sample dispersion) but also on the numerical aperture of the focussing objective in use. These experimental findings on x- and z-cut TFLN are excellently backed up by our advanced numerical simulations.
Keywords: General Physics and Astronomy

Potassium Ion Conductivity in the Cubic Labyrinth of a Piezoelectric, Antiferromagnetic Oxoferrate(III) Tellurate(VI) - Albrecht, Ralf; Hoelzel, Markus; Beccard, Henrik; Rüsing, Michael; Eng, Lukas; Doert, Thomas; Ruck, Michael (Chemistry – A European Journal)
Orange-colored crystals of the oxoferrate tellurate K12+6xFe6Te4−xO27 [x=0.222(4)] were synthesized in a potassium hydroxide hydroflux with a molar water–base ratio n(H2O)/n(KOH) of 1.5 starting from Fe(NO3)3 ⋅ 9H2O, TeO2 and H2O2 at about 200 °C. By using (NH4)2TeO4 instead of TeO2, a fine powder consisting of microcrystalline spheres of K12+6xFe6Te4−xO27 was obtained. K12+6xFe6Te4−xO27 crystallizes in the acentric cubic space group Iurn:x-wiley:09476539:media:chem202102464:chem202102464-math-0001 3d. [FeIIIO5] pyramids share their apical atoms in [Fe2O9] groups and two of their edges with [TeVIO6] octahedra to form an open framework that consists of two loosely connected, but not interpenetrating, chiral networks. The flexibility of the hinged oxometalate network manifests in a piezoelectric response similar to that of LiNbO3.The potassium cations are mobile in channels that run along the <111> directions and cross in cavities acting as nodes. The ion conductivity of cold-pressed pellets of ball-milled K12+6xFe6Te4−xO27 is 2.3×10^(−4) S ⋅ cm^(−1) at room temperature. Magnetization measurements and neutron diffraction indicate antiferromagnetic coupling in the [Fe2O9] groups.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Quantifying the refractive index of ferroelectric domain walls in periodically poled LiNbO3 single crystals by polarization-sensitive optical coherence tomography - Golde, Jonas; Rüsing, Michael; Rix, Jan; Eng, Lukas M.; Koch, Edmund (Optics Express)
Domain walls (DWs) in ferroelectric (FE) and multiferroic materials possess an ever-growing potential as integrated functional elements, for instance in optoelectronic nanodevices. Mandatory, however, is the profound knowledge of the local-scale electronic and optical properties, especially at DWs that are still incompletely characterized to date. Here, we quantify the refractive index of individual FE DWs in periodically-poled LiNbO 3 (PPLN) single crystals. When applying polarization-sensitive optical coherence tomography (PS-OCT) at 1300 nm using circular light polarization, we are able to probe the relevant electro-optical properties close to and at the DWs, including also their ordinary and extraordinary contributions. When comparing to numerical calculations, we conclude that the DW signals recorded for ordinary and extraordinary polarization stem from an increased refractive index of at least Δn > 2·10 −3 that originates from a tiny region of < 30 nm in width. PS-OCT hence provides an extremely valuable tool to decipher and quantify subtle changes of refractive index profiles for both inorganic and biomedical nanomaterial systems.
Keywords: Atomic and Molecular Physics; and Optics

Broadband coherent anti-Stokes Raman scattering for crystalline materials - Hempel, Franz; Reitzig, Sven; Rüsing, Michael; Eng, Lukas M. (Physical Review B)
Broadband coherent anti-Stokes Raman scattering (B-CARS) has emerged in recent years as a promising chemosensitive high-speed imaging technique. B-CARS allows for the detection of vibrational sample properties in analogy to spontaneous Raman spectroscopy, but also makes electronic sample environments accessible due to its resonant excitation mechanism. Nevertheless, this technique has only gained interest in the biomedical field so far, whereas CARS investigations on solid-state materials are rare and concentrate on layered, two-dimensional materials such as graphene and hexagonal boron nitride . In this work, we discuss the specific properties of this technique when applied to single-crystalline samples, with respect to signal generation, phase matching, and selection rules in the model systems lithium niobate and lithium tantalate. Via polarized B-CARS measurements and subsequent phase retrieval, we validate the predicted selection rules, unequivocally assign the phonons of the A1(TO), E(TO) and A1(LO) branches to the detected CARS peaks, and address differences in spontaneous Raman spectroscopy concerning peak frequencies and scattering efficiencies. We thus establish this technique for future investigations of solid-state materials, specifically in the field of ferroelectric single crystals.

Nonlinear focal mapping of ferroelectric domain walls in LiNbO3: Analysis of the SHG microscopy contrast mechanism - Spychala, K. J.; Mackwitz, P.; Rüsing, Michael; Widhalm, A.; Berth, Gerhard; Silberhorn, Christine; Zrenner, Artur (Journal of Applied Physics)

Characterisation of width-dependent diffusion dynamics in rubidium-exchanged KTP waveguides - Padberg, Laura; Santandrea, Matteo; Rüsing, Michael; Brockmeier, Julian; Mackwitz, Peter; Berth, Gerhard; Zrenner, Artur; Eigner, Christof; Silberhorn, Christine (Optics Express)

Resource‐Efficient Low‐Temperature Synthesis of Microcrystalline Pb2B5O9X (X = Cl, Br) for Surfaces Studies by Optical Second Harmonic Generation - Tan, Deming; Kirbus, Benjamin; Rüsing, Michael; Pietsch, Tobias; Ruck, Michael; Eng, Lukas M. (Small)
Optically nonlinear Pb2B5O9X (X = Cl, Br) borate halides are an important group of materials for second harmonic generation (SHG). Additionally, they also possess excellent photocatalytic activity and stability in the process of dechlorination of chlorophenols, which are typical persistent organic pollutants. It would be of great interest to conduct in situ (photo‐) catalysis investigations during the whole photocatalytic process by SHG when considering them as photocatalytic materials. In order to get superior photocatalytic efficiency and maximum surface information, small particles are highly desired. Here, a low‐cost and fast synthesis route that allows growing microcrystalline optically nonlinear Pb 2 B 5 O 9 X borate halides at large quantities is introduced. When applying the ionothermal growth process at temperatures between 130 and 170 °C, microcrystallites with an average size of about 1 µm precipitate with an orthorhombic hilgardite‐like borate halide structure. Thorough examinations using powder X‐ray diffraction and scanning electron microscopy, the Pb2B5O9X microcrystals are indicated to be chemically pure and single‐phased. Besides, the Pb2B5O9X borate halides' SHG efficiencies are confirmed using confocal SHG microscopy. The low‐temperature synthesis route thus makes these borate halides a highly desirable material for surface studies such as monitoring chemical reactions with picosecond time resolution and in situ (photo‐) catalysis investigations.
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Shallow-etched thin-film lithium niobate waveguides for highly-efficient second-harmonic generation - Zhao, Jie; Rüsing, Michael; Javid, Usman A.; Ling, Jingwei; Li, Mingxiao; Lin, Qiang; Mookherjea, Shayan (Optics Express)
High-fidelity periodic poling over long lengths is required for robust, quasi-phase-matched second-harmonic generation using the fundamental, quasi-TE polarized waveguide modes in a thin-film lithium niobate (TFLN) waveguide. Here, a shallow-etched ridge waveguide is fabricated in x-cut magnesium oxide doped TFLN and is poled accurately over 5 mm. The high fidelity of the poling is demonstrated over long lengths using a non-destructive technique of confocal scanning second-harmonic microscopy. We report a second-harmonic conversion efficiency of up to 939 %/W (length-normalized conversion efficiency 3757 %/Wcm²), measured at telecommunications wavelengths. The device demonstrates a narrow spectral linewidth (1 nm) and can be tuned precisely with a tuning characteristic of 0.1 nm/°C, over at least 40 °C without measurable loss of efficiency.
Keywords: Atomic and Molecular Physics; and Optics

Poling thin-film x-cut lithium niobate for quasi-phase matching with sub-micrometer periodicity - Zhao, Jie; Rüsing, Michael; Roeper, Matthias; Eng, Lukas M.; Mookherjea, Shayan (Journal of Applied Physics)
Quasi-phase-matched grating structures in lithium niobate waveguides with sub-micrometer periodicities will benefit the development of short-wavelength nonlinear optical devices. Here, we report on the reproducible formation of periodically poled domains in x-cut single-crystalline thin-film lithium niobate with periodicities as short as 600 nm. Shaped single-voltage poling pulses were applied to electrode structures that were fabricated by a combination of electron-beam and direct-writing laser lithography. Evidence of successful poling with good quality was obtained through second-harmonic microscopy and piezoresponse force microscopy imaging. For the sub-micrometer period structures, we observed patterns with a double periodicity formed by domain interactions and features with sizes <200 nm.
Keywords: General Physics and Astronomy

High Quality Entangled Photon Pair Generation in Periodically Poled Thin-Film Lithium Niobate Waveguides - Zhao, Jie; Ma, Chaoxuan; Rüsing, Michael; Mookherjea, Shayan (Physical Review Letters)
Keywords: General Physics and Astronomy

Periodic Poling of X-Cut Thin-Film Lithium Niobate: The Route to Submicrometer Periods - Rüsing, Michael; Roeper, M.; Amber, Z.; Kirbus, B.; Eng, L.M.; Zhao, J.; Mookherjea, S. (2020 Joint Conference of the IEEE International Frequency Control Symposium and International Symposium on Applications of Ferroelectrics (IFCS-ISAF))

micro-Raman Investigations of Periodically-Poled X-Cut Thin-Film Lithium Niobate for Integrated Optics - Reitzig, Sven; Rüsing, Michael; Kirbus, Benjamin; Gossel, Joshua; Singh, Ekta; Eng, Lukas M.; Zhao, Jie; Mookherjea, Shayan (2020 Joint Conference of the IEEE International Frequency Control Symposium and International Symposium on Applications of Ferroelectrics (IFCS-ISAF))

Second harmonic microscopy of poled x-cut thin film lithium niobate: Understanding the contrast mechanism - Rüsing, Michael; Zhao, J.; Mookherjea, S. (Journal of Applied Physics)
Thin film lithium niobate has been of great interest recently, and an understanding of periodically poled thin films is crucial for both fundamental physics and device developments. Second-harmonic (SH) microscopy allows for the noninvasive visualization and analysis of ferroelectric domain structures and walls. While the technique is well understood in bulk lithium niobate, SH microscopy in thin films is largely influenced by interfacial reflections and resonant enhancements, which depend on film thicknesses and substrate materials. We present a comprehensive analysis of SH microscopy in x-cut lithium niobate thin films, based on a full three-dimensional focus calculation and accounting for interface reflections. We show that the dominant signal in backreflection originates from a copropagating phase-matched process observed through reflections, rather than direct detection of the counterpropagating signal as in bulk samples. We simulate the SH signatures of domain structures by a simple model of the domain wall as an extensionless transition from a −χ(2) to a +χ(2) region. This allows us to explain the main observation of domain structures in the thin-film geometry, and, in particular, we show that the SH signal from thin poled films allows to unambiguously distinguish areas, which are completely or only partly inverted in depth.
Keywords: General Physics and Astronomy

Toward 3D Integrated Photonics Including Lithium Niobate Thin Films: A Bridge Between Electronics, Radio Frequency, and Optical Technology - Rüsing, Michael; Weigel, Peter O.; Zhao, Jie; Mookherjea, Shayan (IEEE Nanotechnology Magazine)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering

Optical diagnostic methods for monitoring the poling of thin-film lithium niobate waveguides - Zhao, Jie; Rüsing, Michael; Mookherjea, Shayan (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Achieving beyond-100-GHz large-signal modulation bandwidth in hybrid silicon photonics Mach Zehnder modulators using thin film lithium niobate - Wang, Xiaoxi; Weigel, Peter O.; Zhao, Jie; Rüsing, Michael; Mookherjea, Shayan (APL Photonics)
Mach-Zehnder electro-optic modulators (EOM) based on thin-film lithium niobate bonded to a silicon photonic waveguide circuit have been shown to achieve very high modulation bandwidths. Open eye-diagram measurements made in the time domain of beyond-small-signal modulation are used to support the modulation-sideband measurements in showing that such EOM’s can support high-frequency modulations well beyond 100 GHz.
Keywords: Computer Networks and Communications; Atomic and Molecular Physics; and Optics